Rosalía pensada por Torres Queiruga: una interpretación - SERANTES, M.ª Aránzazu (Madrygal. Revista de Estudios Gallegos, 2010)
The philosopher and theologist Andrés Torres Queiruga has dedicateds some articles to reflect different and original points of view about Rosalía de Castro. In some of them he defended that Rosalía is a metaphysical poet who received influences of her enviroment: personal life, history, politics, etc and she converted her `vital´ experiences into poetic language. Rosalía is described, in general, with topics and stereotypical definitions. But this image is almost unreal because her attitude was revolutionary, in terms of populist leanings, sympathy for women and also the most important concern, Galicia. Popular oral were described for Rosalía with a particular feeling called `saudade ´, a new way for reason that unifies spirit and reality. In this work I would like to explain the most recently arguments that Torres Queiruga defends. His writings about Rosalía has not been studied very much, for this reason, I would like to offer a synthetical view of his thought.